A New Design of Access Control in Wireless Sensor Networks. (26th April 2011) - Huang, Hui-Feng
Abstract : Nodes in a sensor network may be lost because of power exhaustion or malicious attacks. To extend the span of sensor network, new nodes deployment is necessary. To prevent malicious nodes from joining the sensor networks, access control is a designed requirement for controlling sensor node deployment. Based on elliptic curve cryptography (ECC), this paper presents a new access control protocol for secure wireless sensor networks. The proposed scheme not only prevents malicious nodes from joining sensor networks, but also key establishment is included in the authentication procedure. Compared to the previously proposed schemes, the authentication procedure and common key generation of the proposed method are very simple and efficient. It could offer computational efficiency, energy, and bandwidth savings. In addition, it can be easily implemented as a dynamic access control, because all the old secret keys and information in existing nodes should not be updated once a new node is added or an old node is lost.